The emerging phenotype of nonalcoholic fatty liver disease in lean individuals: what’s different? - Dey, Priyankar (Frontiers in Endocrinology, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD), currently referred to as metabolic dysfunction-associated steatotic liver disease (MASLD), occurring in adults of normal weight, represents a unique emerging phenotype apart from obesity-related NAFLD. Notwithstanding a normal body mass index (BMI), this phenotype poses considerable metabolic and hepatic risk, undermining conventional obesity-focused paradigms of fatty liver disease.MethodsThis comprehensive review integrates global epidemiological data, molecular investigations, and clinical research to elucidate the distinct pathogenesis, risk factors, natural history, and treatment of lean NAFLD. Essential bibliographical databases were screened for research on disease prevalence, genetic determinants, metabolic characteristics, and long-term consequences.ResultsLean NAFLD impacts 5-20% of the worldwide NAFLD population, with a greater frequency in Asian cohorts (~45%). It is characterized by visceral obesity, sarcopenia, and significant genetic determinants (variants of PNPLA3, TM6SF2, and MBOAT7) in normal BMI individuals. Gut dysbiosis and modified bile acid metabolism further delineate its pathophysiology. Importantly, lean NAFLD presents similar or elevated risks for all-cause mortality (1.6-fold increase), advanced fibrosis, cirrhosis, hepatocellular carcinoma, and cardiovascular disease compared to obese NAFLD, despite a lower prevalence of metabolic comorbidities.ConclusionLean NAFLD is a clinically relevant condition necessitating customized diagnostic and therapeutic approaches. Lifestyle modifications focusing on moderate weight reduction (3-5%), fructose and cholesterol restrictions, and resistance exercise are highlighted. Future investigations should emphasize consistent classifications, non-invasive biomarkers, and medicines tailored to lean NAFLD phenotypes.